Farmers organizing farmers: a methodological study of Farmer Irrigators' Organization Program in the Philippines - Wijayaratna, C.M.; Pintor, E.M.; Valdéz, D.M.; Laitos, R..W; Solis, V.V. (International Irrigation Management Institute, 1996)
The study, conducted in the Philippines, was aimed at developing and testing an integrated research methodology combining Process Documentation Research PDR and validation of PDR findings through a quick process of workshops and questionnaire surveys to assess the Farmer Irrigators' Organization Program (FIOP) country-wide. PDR using an action research mode, was confined to a small sample and provided continuous feedback during FIOP implementation. On the other hand, because of the large sample size and area covered the workshops and questionnaire surveys were useful in validating quantitatively the more qualitative PDR findings. The validation process was quick because it was guided by PDR results. Hence methods used are complementary to each other and can be integrated.